The Rural Immersion program: developing a resident-driven residency program - Niburski, Kacper; Jawanda, Nicholas (Canadian Medical Education Journal, 2025)
Implication Statement: The Rural Immersion program has been created to streamline residents to less-used remote sites, and to create resident-driven curriculums. The program is suggested as a possible means to increase rural retention and benefit rural communities with longitudinal follow up. It has attracted residents and will officially begin July 2024.